2013
DOI: 10.1108/mrr-04-2012-0077
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of acquisitions: an Indian perspective

Abstract: PurposeThe purpose of this paper is to identify and investigate firm level determinants of the firm's decision on acquisition strategy.Design/methodology/approachA total of 360 firms across fast growing sectors in India, namely automobile, FMCG and pharmaceutical were selected for six years, i.e. from 2004‐2010, thus making a sample of 360 firms. Hypothesis were tested using panel logit regression and instrumental IV variable regression.FindingsFindings suggest that earnings volatility and business group affil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…M&A can be one of the appropriate strategies to increase the market share of firms, improve profitability, acquire resources which further reduce the earning volatility. This was supported by Agnihotri (2013), that the firms experiencing high earning volatility take this as a crucial matter and acquirer firms thereby acquire the resources and assets which recovers its earnings. Aevoae, Dicu, and Mardiros (2018), found that certain target firms applied GAAP (Generally Accepted Accounting Principles) in reporting the financial statements and other target firms used IFRS (International Financial Reporting Standards), and the acquirers were found to be looking for related companies which are reporting profits accurately as well as the productivity of employees found to be high.…”
Section: Volatility Of Earningsmentioning
confidence: 89%
“…M&A can be one of the appropriate strategies to increase the market share of firms, improve profitability, acquire resources which further reduce the earning volatility. This was supported by Agnihotri (2013), that the firms experiencing high earning volatility take this as a crucial matter and acquirer firms thereby acquire the resources and assets which recovers its earnings. Aevoae, Dicu, and Mardiros (2018), found that certain target firms applied GAAP (Generally Accepted Accounting Principles) in reporting the financial statements and other target firms used IFRS (International Financial Reporting Standards), and the acquirers were found to be looking for related companies which are reporting profits accurately as well as the productivity of employees found to be high.…”
Section: Volatility Of Earningsmentioning
confidence: 89%
“…Agnihotri [5] investigate and analyzed determinants of acquisitions in three industries in India and find that the volatility of earnings and business group affiliation has a significant influence on acquisitions by Indian firms.The paper focused more on increase in earnings due to Acquisitions.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Agnihotri [7] found that the acquisition decision of a firm is determined significantly by earnings volatility and business group affiliation in India. A sample of 360 firms, spanning three fast-growing sectors, was chosen for the period 2004-10.…”
Section: Aim Of the Papermentioning
confidence: 99%